2022
DOI: 10.7860/jcdr/2022/56112.16652
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Risk among Healthcare Workers in DCH and DCHC Hospitals during COVID-19 Duty: Correlation of Stress Score with Blood Pressure and Lipid Profile

Abstract: Introduction: Healthcare workers (HCW’s) are at the frontline of the Coronavirus Disease-2019 (COVID-19) pandemic, participating directly in the diagnosis and treatment of Coronavirus patients for the past two years. This puts them at a larger risk of causing long-term stress, mental anguish, and other negative psychological impacts. Aim: To evaluate stress score, serum lipid profile and blood pressure in a Dedicated COVID Hospital (DCH) and Dedicated COVID Health centre (DCHC) among HCWs, and to correlate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Sawai et al [ 20 ] found that mental stress has an influence on the plasma homocysteine level and blood pressure variation. A recent hospital-based study from India reported that work stress was strongly correlated with the blood lipid profile and blood pressure of 40 HCWs aged 25–40 years who had direct contact with COVID-19 patients [ 21 ]; the authors considered physical and psychological stress caused by the COVID-19 assignment as a risk factor in increased triglyceride and low-density lipoprotein levels and decreased high-density lipoprotein levels. Alameri et al used electronic surveys in hospitals and healthcare institutions in Abu Dhabi for a cross-sectional investigation and reported correlations between burnout severity and cardiovascular risk in healthcare professionals during the COVID-19 pandemic [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sawai et al [ 20 ] found that mental stress has an influence on the plasma homocysteine level and blood pressure variation. A recent hospital-based study from India reported that work stress was strongly correlated with the blood lipid profile and blood pressure of 40 HCWs aged 25–40 years who had direct contact with COVID-19 patients [ 21 ]; the authors considered physical and psychological stress caused by the COVID-19 assignment as a risk factor in increased triglyceride and low-density lipoprotein levels and decreased high-density lipoprotein levels. Alameri et al used electronic surveys in hospitals and healthcare institutions in Abu Dhabi for a cross-sectional investigation and reported correlations between burnout severity and cardiovascular risk in healthcare professionals during the COVID-19 pandemic [ 22 ].…”
Section: Discussionmentioning
confidence: 99%